2012
DOI: 10.1051/0004-6361/201219154
|View full text |Cite
|
Sign up to set email alerts
|

First LOFAR observations at very low frequencies of cluster-scale non-thermal emission: the case of Abell 2256

Abstract: Abell 2256 is one of the best known examples of a galaxy cluster hosting large-scale diffuse radio emission that is unrelated to individual galaxies. It contains both a giant radio halo and a relic, as well as a number of head-tail sources and smaller diffuse steep-spectrum radio sources. The origin of radio halos and relics is still being debated, but over the last years it has become clear that the presence of these radio sources is closely related to galaxy cluster merger events. Here we present the results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…Additionally, the classical hadronic model cannot reproduce some spectral features observed in clus-ters, such as the total spectral (convex) curvature claimed in the Coma RH or the spectral steepening observed at the boundary of some RHs. However, the recent report of spectral flattening with frequency of the RH in A2256 (van Weeren et al 2012) could easily be accommodated in the hadronic model, which naturally produces such a concave spectrum (Pinzke & Pfrommer 2010). This raises the interesting question whether such a variability among different sources that are generally classified as "radio halos" signals the presence of richer underlying physics-a question that we will address in this paper.…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, the classical hadronic model cannot reproduce some spectral features observed in clus-ters, such as the total spectral (convex) curvature claimed in the Coma RH or the spectral steepening observed at the boundary of some RHs. However, the recent report of spectral flattening with frequency of the RH in A2256 (van Weeren et al 2012) could easily be accommodated in the hadronic model, which naturally produces such a concave spectrum (Pinzke & Pfrommer 2010). This raises the interesting question whether such a variability among different sources that are generally classified as "radio halos" signals the presence of richer underlying physics-a question that we will address in this paper.…”
Section: Introductionmentioning
confidence: 95%
“…A steepening of the halo spectrum with frequency is noticed in Abell 3562 and Abell 2256 (Giacintucci et al 2005;van Weeren et al 2012b). The turbulent acceleration model with particles emitting in a region with relatively uniform magnetic field intensity was invoked to explain the high frequency steepening in Abell 3562 while the low frequency steepening in Abell 2256 was explained with inhomogeneous turbulence.…”
Section: Flux Measurements and Integrated Radio Spectramentioning
confidence: 86%
“…For a few relics the injection spectral indices derived from the integrated spectral indices are even flatter than allowed by DSA test particle theory, i.e. spectra have been found flatter than −0.5, for example in A2256 (van Weeren et al 2012b;Trasatti et al 2015) and CIZA J2242.8+5301 (Kierdorf et al 2016;Hoang et al 2017). The derived integrated spectral index of relics B, D and E are consistent with the DSA approximation.…”
Section: Flux Measurements and Integrated Radio Spectramentioning
confidence: 99%
“…From the medium flux ratio we determine a difference in flux scale of about a factor 0.8 between LOFAR and the GMRT. Such differences are not unexpected given the uncertainties in the calibration of the low frequency fluxscale with the GMRT (which is estimated to be about 10%, Intema et al 2011) and the complex LOFAR station beams (van Weeren et al 2012b(van Weeren et al , 2014. Recently, it has been found that the normalization of the LOFAR HBA beam was not correctly implemented in the models (work is ongoing to fix this issue).…”
Section: Accuracy Of the Flux-scale Bootstrappingmentioning
confidence: 99%